Anti-inflammatory effect of tranexamic acid on adult cardiac surgical patients: A PRISMA-compliant systematic review and meta-analysis - Chunmei, Xie; Yuntai, Yao; Lixian, He; Ke, Yang (Frontiers in Surgery, 2022)
Objective This study aims to evaluate the anti-inflammatory effect of tranexamic acid (TXA) on adult cardiac surgical patients. Methods PubMed, Embase, Ovid, Web of Science, CNKI, VIP, and WANFANG databases were systematically searched using the related keywords for cardiac surgical randomized controlled trials (RCTs) published from their inception to February 1, 2022. The primary outcomes were postoperative inflammatory biomarkers levels. The secondary outcomes were postoperative systemic inflammatory response syndrome and other major postoperative outcomes. The odds ratios and/or the weighted mean difference (WMD) with a 95% confidence interval (CI) were used to pool the data. Results Ten RCTs with 770 adult cardiac surgical patients were included. Compared with placebo, TXA achieved statistically significant inhibition of the postoperative interleukin (IL)-6 level (postoperative 6 h: n = 6 trials; WMD −31.66; 95% CI: −45.90, −17.42; p < 0.0001; I2 = 93%; postoperative 24 h: n = 8 trials; WMD, −44.06; 95% CI: −69.21, −18.91; p = 0.006; I2 = 100%); IL-8 level postoperative 24 h, TNF-α level postoperative 24 h, NE level postoperative 6 h: n = 3 trials; WMD, −36.83; 95% CI: −68.84, −4.83; p = 0.02; I2 = 95%); tissue necrosis factor alpha (TNF-α) level (postoperative 6 h: n = 3 trials; WMD, −7.21; 95% CI: −12.41, −2.01; p = 0.007; I2 = 47%; postoperative 24 h: n = 5 trials; WMD, −10.02; 95% CI: −14.93, −5.12; p < 0.0001; I2 = 94%); and neutrophil elastase (NE) level (postoperative 6 h: n = 3 trials; WMD, −66.93; 95% CI: −111.94, −21.92; p = 0.004; I2 = 86%). However, TXA achieved no statistically significant influence on the postoperative 24 h NE level. Conclusions TXA had a significant anti-inflammatory effect in adult cardiac surgical patients, as evidenced by the reduction of multiple postoperative proinflammatory biomarkers levels, but these results should be interpreted carefully and cautiously, as only a limited number of studies were included and there was high heterogeneity between them. Systematic Review Registration https://www.crd.york.ac.uk/prospero/#recordDetails, identifier: CRD42022312919.